The Needs ABC Therapeutic Model for Couples and Families : a Guide for Practitioners. - Caplan, Tom (Taylor & Francis, 2010)
The Needs ABC Therapeutic Model for Couples and Families provides beginning clinicians with concrete, practical skills and expanded theoretical base for their practice. Readers€will€be able to apply their new knowledge directly and in ways that will help them create long-lasting change in clients who present with difficult behaviors.